Robot Navigation Planning Problems in Dynamic Environments - Urniezius, R.; Bartkevicius, S. (Elektronika ir Elektrotechnika, 2008)
Main robot navigation planning methods and approaches of the dynamic environment are discussed. While considering approaches, performance, the possibility of redundant motions and optimal path existence are taken into account. During path planning the compromise between maximum clearance to obstacles and the shortest path to the destination is discussed. Multi-robot planning is viewed as an offline planning problem with prioritized approach. Planning for unpredictable obstacles and probabilistic routines for known environments including repetitive motions is reviewed. Ill. 4, bibl. 6 (in English; summaries in English, Russian and Lithuanian).